Polydatin Inhibits Cell Viability, Migration, and Invasion Through Suppressing the c-Myc Expression in Human Cervical Cancer - Bai, Longchang; Ma, Yingkang; Wang, Xue; Feng, Qiongni; Zhang, Zhining; Wang, Sijie; Zhang, Huijie; Lu, Xinyu; Xu, Yonghui; Zhao, Erhu; Cui, Hongjuan (Frontiers in Cell and Developmental Biology, 2021)
Polydatin, an active ingredient from roots of Polygonum cuspidatum, is considerated to have cardiovascular and liver protection functions. In this study, we demonstrated that polydatin has an anticancer activity in human cervical cancer. Polydatin efficiently inhibited cervical cancer cell proliferation by regulating cell cycle-related proteins including p21, p27, CDK2, CDK4, Cyclin D1 and Cyclin E1. Meanwhile, polydatin suppressed cell invasion and migration by regulating the epithelial-mesenchymal transition (EMT) markers including E-cadherin, N-cadherin and Snail. The c-Myc, as a proto-oncogene, is considered to be closely related to the proliferation and metastasis of tumor cells. After polydatin treatment, the expression of c-Myc protein showed a significant decline. Based on these data, we overexpressed c-Myc in cervical cancer cells and noticed that overexpression of c-Myc rescued the inhibitory effect of polydatin on cell proliferation and metastasis. These results indicated that polydatin can inhibit cell proliferation and metastasis by down-regulating c-Myc in human cervical cancer.